Quantisation of Black hole horizon area and multipartite entanglement of Black hole information subsystems - Noor, Mehdi Salman; Jahan, Sayeda Tashnuba (Brac University, 2020)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Physics.